2022
DOI: 10.1111/ppa.13531
|View full text |Cite
|
Sign up to set email alerts
|

A review on the potential effects of temperature on fungicide effectiveness

Abstract: Fungicides are one possible way to manage fungal and oomycete plant pathogens in order to safeguard yield and quality of crops and to improve shelf‐life of produce in agriculture and horticulture. However, global warming and the resulting temperature increase may affect the effectiveness of some important fungicides, including efficacy and duration of plant disease control. Nevertheless, according to our literature survey, there is little specific information available on whether and how temperature influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…In three out of eleven years, no significant differences in root yield were found as a result of the foliar application of fungicides. The effectiveness of fungicide application was found to be heavily dependent on climatic conditions also by Greiner et al [46] and Juroszek et al [47]. However, in our own research, this is confirmed by correlation calculations.…”
Section: Discussionsupporting
confidence: 84%
“…In three out of eleven years, no significant differences in root yield were found as a result of the foliar application of fungicides. The effectiveness of fungicide application was found to be heavily dependent on climatic conditions also by Greiner et al [46] and Juroszek et al [47]. However, in our own research, this is confirmed by correlation calculations.…”
Section: Discussionsupporting
confidence: 84%
“…While some higher altitude or latitude locations may benefit from this change, these will likely be the exception [7]. Plant protection and plant biosecurity may also be adversely impacted [8][9][10][11], and thus, improved biosecurity measures and climate-smart plant protection methods will be needed [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change, particularly global warming and altered precipitation patterns, could directly and indirectly influence plant pathogens and their host plants, thereby altering the spatial distribution, temporal occurrence, incidence and severity of crop diseases worldwide (Bebber et al, 2013; Garrett et al, 2022; Krengel‐Horney et al, 2021; Newbery et al, 2016; Richard et al, 2022; West et al, 2012). Disease management strategies in agriculture and horticulture could also be affected (IPPC Secretariat, 2021); consequently, affected ones may require appropriate adjustments in the future (Heeb et al, 2019; Juroszek & von Tiedemann, 2011), including plant disease resistance breeding (Miedaner & Juroszek, 2021a, 2021b) and fungicide use (Juroszek et al, 2022). For example, increasing temperature can reduce the efficacy level of host plant resistance (Desaint et al, 2021).…”
Section: Introductionmentioning
confidence: 99%